Physical activity throughout adolescence and HbA1c in early adulthood: Birth cohort study - Nakamura, Priscila M. [UNESP]; Mielke, Grégore I.; Horta, Bernardo L.; Assunção, Maria Cecília; Gonçalves, Helen; Menezes, Ana M.B.; Barros, Fernando C.; Ekelund, Ulf; Brage, Soren; Wehrmeister, Fernando C.; Oliveira, Isabel O.; Hallal, Pedro C. (Human Kinetics, 2017)
Background: Physical inactivity is responsible for 7% of diabetes deaths worldwide, but little is known whether low levels of physical activity (PA) during adolescence increase the risk of diabetes in early adulthood. We evaluated the cross-sectional and longitudinal associations between PA throughout adolescence and HbA1c concentration in early adulthood. Methods: HbA1c was measured by high performance liquid chromatography. PA was assessed by self-report at the ages of 11, 15, and 18 years and by accelerometry at the ages of 13 (subsample) and 18 years. The loss percentages of follow up were 12.5% at 11 years, 14.4% at 15 years, and 18.7% at 18 years. Results: At 18 years, boys showed higher HbA1c than girls. At age 18 years, accelerometrybased PA at 18 years was inversely related to HbA1c levels in boys. Self-reported leisure-time PA at ages 11, 15, and 18 were unrelated to HbA1c in both genders. PA at 13 years of age was unrelated to HbA1c among both genders. In trajectory analysis, PA and accelerometer PA trajectories were not associated with later HbA1c. Conclusion: Objectively measured PA at 18 years was cross-sectionally inversely associated with HbA1c in boys only. No prospective associations were identified.
Keywords: Brazil; Glycosylated hemoglobin; Longitudinal study; Motor activity